Calibration of dynamic tool–workpiece interface temperature measurement during friction stir welding. (June 2016) - Schmale, Joshua; Fehrenbacher, Axel; Shrivastava, Amber; Pfefferkorn, Frank E.
Abstract: The objective of this work is to accurately measure the transient temperatures at the tool–workpiece interface during friction stir welding (FSW) using thermocouples that are embedded in the tool. Temperature sensors embedded in the friction stir (FS) tool provide a non-consumable localized temperature measurement capability that is crucial for process research, development, and control. A modification of the ASTM E-1461 standard for measuring thermal diffusivity with pulses of heat flux is proposed for calibrating the transient response of temperature sensors located near the surface of the FS tool. These tests enable the calculation of each sensor's time constant, which are used in one-dimensional analytical models of the dynamic response to calculate the true interface temperature. Time constants between 21 and 43 ms are measured for 0.25-mm-diameter, sheathed thermocouples located at the FS tool surface.